Pengaruh Nilai Pemasaran dan Harga Jual Rumah di Perumahan Bukaka Residance Terhadap Keputusan Pembeli - Suwanti, Ratih (Pascasarjana STIE Amkop Makassar, 2024)
The results of this study indicate that based on the partial employees, physical evidence and processes have a positive and significant effect, while the results of the simultaneous test of products, prices, employees, physical evidence and processes have a positive and significant effect. simultaneous positive and insignificant effect on Customer Decisions home sales. Kata Kunci: Marketing, Price, Place, Promotion, Sales, Physical Evidence, Process and Costumer Decisions